Compliance with the Australian 24-hour movement guidelines for the early years: associations with weight status - Santos, Rute (2017)
Background: For effective public health and surveillance it is important to document the proportion of young children who meet the new Australian Integrated 24 h Movement Guidelines for the Early Years and how these associate with health outcomes. We aimed to (i) assess compliance with the new Integrated 24 h Movement Guidelines for the Early Years in a sample of Australian toddlers; and (ii) ascertain whether compliance with the guidelines associates with weight status. Methods: The sample comprised 202 toddlers (104 girls) aged 19.74 ± 4.07 months from the GET UP! Study. Participants wore accelerometers (Actigraph GT3X+) for 24 h over 7 consecutive days to assess physical activity, sedentary time and sleep. Parents reported participants’ screen time. Weight and height were measured and body mass index (BMI) z-scores by age and sex were calculated. Analysis of Covariance (ANCOVA) was performed to test differences in BMI z-scores between participants complying with (i) none or any individual guideline, (ii) any combination of meeting two guidelines, and (iii) those who met all three guidelines, adjusting for child age, gender and socioeconomic status. Results: Only 8.9% of the sample met the overall 24 h movement guidelines. Most of the sample met the physical activity (96.5%) and sleep (79.7%) guidelines but only 11.4% met the sedentary behavior guideline. Average BMI Z-scores did not significantly differ between children who complied with none or any individual guideline, any combination of meeting two guidelines, and those who met all three guidelines (p > 0.05). Although the lack of significant differences, participants who accomplished any combination of two guidelines or all three guidelines appear to have had a lower BMI Z-score than those complying with one of the guidelines or none. Conclusions: Just under 9% of our sample met the overall Australian 24 h Movement Guidelines for the Early Years. BMI was not associated with the accomplishment of any of the 24-h Movement Guidelines. Strategies to promote adherence to the 24-h movement guidelines in toddlers, particularly for screen time, are necessary, as promoting health-related behaviors in early childhood has the potential to provide children a strong foundation for lifelong physical and mental health.